Research methods for leisure, recreation and tourism (CABI, 2011)
This introductory level textbook describes fundamental elements of research methods for leisure, recreation and tourism, with contributions from internationally renowned and active researchers in the field. It covers statistical information such as measurement of variables, sampling, questionnaire design and evaluation methods, and also contains wider discussion of writing proposals, communicating research findings, cross-cultural research, and the use of new technologies in conducting research. Enhanced by illustrations, focus boxes, review questions and case studies, this text introduces undergraduate students to the vital skills they will need to succeed in tourism studies.